Anna of Denmark : the Material and Visual Culture of the Stuart Courts, 1589-1619 - Field, Jemma (Studies in Design and Material Culture Ser., 2020)
This book examines Anna of Denmark's engagement with visual and material goods, including architecture, garden design, painting and jewellery. It contextualises the consort's place within the wider socio-political environment of the Stuart courts and provides a comprehensive understanding of her personal iconography, aims, interests and alliances.